MALASSEZİA TÜRLERİ: TAKSONOMİ, MİKOLOJİ, İMMUNOLOJİ, PATOGENEZ, VÜCUTTAKİ DAĞILIMI VE İLİŞKİLİ İNFEKSİYONLAR, LABORATUVAR TANIMI, ANTİFUNGALLERE DUYARLILIĞI - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Malassezia is a dimorphic fungus which forms part of the normal skin flora, it may exist as budding yeasts in stratum corneum in patients with several cutaneous disease and can cause iatrogenic systemic infections such as fungemia, pulmonary vasculitis, peritonitis in predisposed neonates, children and adults. Malassezia may induce humoral and cellular immunity via activating the classical and alternative pathways of complement system and also is able to downregulate the immune response in some circumstances, thus, the fungus exists at the very interface between the commensalism and pathogenicity. High lipid content was reported in the cell wall of immunomodulatory phenotype. Recently, Malassezia was taxonomically reclassified and currently the genus consist eleven species as M. japonica, M. globosa, M. restricta, M. obtusa, M. slooffiae, M. furfur, M.nana, M. sympodialis, M. dermatis, M. pachydermatis and M.yamatoensis. Except M.pachydermatis,Malassezia species are lipophylic. The incidence may be even higher than current reports present due to growth difficulties. Because the distribution of the newly defined species of Malassezia at various sites on human body and their role in pathogenesis is still lacking, the previous studies and reports, antifungal susceptibility data and other features of the fungus has currently been reexamined through new taxonomical status.*Anahtar Kelimeler: Malassezia türleri, lipofilik mayalar, deri florası, fungemi*Key Words: Malassezia species, lipophylic yeasts,skin flora, fungemia